Managing Athlete Anxiety: A Comprehensive Review of Psychological Interventions in Sports Psychology - Abdollahi Dehkordi , Amir Mohammad; Chtourou, Hamdi (Health Nexus, 2023)
Anxiety in athletes is a pivotal factor affecting performance, mental health, and career longevity. This comprehensive review synthesizes current research on psychological interventions aimed at managing athlete anxiety, offering insights into their effectiveness and applicability in sports psychology. Employing a systematic methodology, the review analyzes studies from peer-reviewed journals published between 2010 and 2023, focusing on interventions such as cognitive-behavioral therapy, mindfulness, relaxation techniques, and motivational interviewing. The findings indicate that tailored, context-specific interventions yield the most significant improvements in reducing anxiety and enhancing athletic performance. Moreover, the review highlights the need for holistic approaches that consider individual athlete needs, sport-specific demands, and cultural factors. The synthesis of empirical data suggests that integrating psychological interventions into athletes’ training regimes can lead to positive outcomes in both mental well-being and performance. This review underscores the importance of psychological support in sports and serves as a resource for practitioners and researchers in developing effective strategies for managing athlete anxiety.